Determinants of Interpreting Difficult Classroom Situations by Young People with Mild Intellectual Disability – Case Study Analysis - Kurtek, Paweł (Przegląd Psychologiczny, 2024)
Aim: Effective coping in difficult classroom situations involving peers requires gaining proper social insight. Limited abilities to process information by persons with MID (mild intellectual disability) may undermine the process of causal attribution especially in the context of stressful situations, which most often leads to defensive attribution when the cause for an event is assigned to negative dispositions of the peer. The aim of this paper is to verify the regulatory role of determinants of causal attribution in persons with mild/moderate intellectual disability, proposed as part of the Kelley’s cube model. Method: Case studies were analysed using the phenomenological, qualitative research approach. Results: Interviews conducted with 12 students with MID aged 18 to 24 years showed that low distinctiveness of the subject’s negative behaviour, with simultaneous low consensus and comparison-object consensus of this behaviour, promotes attribution of the cuse to the perpetrator (negative subject). Low consistency of peer’s negative behaviour on the other hand, with comparison-object consensus of this behaviour across the group, fosters situational attribution. Conclusion: The paper ends with the summary and discussion of results, as well as indication of study limitations.